Extra-articular scapular fractures: comparison of theoretical and actual treatment. Issue 1 (January 2016) - Brandsema, Berdien; Neuhaus, Valentin; Gradl, Gertraud; Ring, David C
Background: Discrete radiographic thresholds of scapular fracture deformity proposed as a guide for when to utilize operative treatment are a matter of debate. The purpose of the present study was to determine how many patients would have received operative treatment according to these criteria and how many actually received operative treatment. Methods: Three hundred and thirty patients with an extra-articular fracture of the scapula at two level 1 trauma centers were retrospectively analyzed. Glenopolar angle, translation, angulation and medial/lateral displacement were measured on computed tomogaphy scans or radiographs to determine the theoretical operative treatment recommendation according to Cole's criteria. Results: Sixty-two patients (19%) had one or more radiographic indications for operative treatment, half of them had more than 20 mm of lateral displacement, and one fourth of them had substantial translation. No patients had operative treatment of the scapular body. Two patients had operative treatment of an acromion fracture, neither of which met radiographic criteria for surgery. Conclusions: At least in our centres, there is a striking discrepancy between theoretical and actual recommendations for surgery. There is clearly a need for more research to determine whether patients are being undertreated or whether the guidelines are too stringent.